Best Answer

(-2x3 - 2x2 + 12x) = -2x (x2 + x - 6) = -2x (x + 3) (x - 2)

Q: What is the factorization of the polynomial below -2x3-2x2 plus 12x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x + 5)(x + 2)

It is: (x+1)(x+6) when factored

That would be -2 (x-2) x (x+3). Click on the Wolfram|Alpha link for all of your polynomial factorization needs.

x3 - 7x2 + 6x =x (x2 - 7x + 6) =x (x - 6) (x - 1)

The actual equation itself is the polynomial. There is no polynomial for it, and your question doesn't really make sense.

Related questions

It is (x+2)(x+9) when factored

(x + 2)(3x + 1)

It is 6x(2x+5) when factored

(x + 5)(x + 2)

x3 - 12x2 + 35x = x (x2 - 12x + 35) = x (x - 7) (x - 5)

x² + 8x + 15 = (x + 5)(x + 3)

x + 12x + 20 = (x + 10)(x + 2)

65

88 -Apex ;)

3x2 + 33x + 54 =3(x2 + 11x + 18) = 3(x + 9)(x + 2)

That would be -2 (x-2) x (x+3). Click on the Wolfram|Alpha link for all of your polynomial factorization needs.

10